Predictors of Emerging Suicide Death Among Military Personnel on Social Media Networks. Issue 4 (28th July 2017) - Bryan, Craig J.; Butner, Jonathan E.; Sinclair, Sungchoon; Bryan, Anna Belle O.; Hesse, Christina M.; Rose, Andree E.
Abstract : Suicide is a leading cause of death in the United States and is the second leading cause of death in the U.S. military. Previous research suggests that data obtained from social media networks may provide important clues for identifying at‐risk individuals. To test this possibility, the social media profiles from 315 military personnel who died by suicide ( n = 157) or other causes ( n = 158) were coded for the presence of stressful life situations (i.e., triggers), somatic complaints or health issues (i.e., physical), maladaptive or avoidant coping strategies (i.e., behaviors), negative mood states (i.e., emotion), and/or negative cognitive appraisals (cognition). Content codes were subsequently analyzed using multilevel models from a dynamical systems perspective to identify temporal change processes characteristic of suicide death. Results identified temporal sequences unique to suicide, notably social media posts about triggers followed by more posts about cognitions, posts about cognitions followed by more posts about triggers, and posts about behaviors followed by fewer posts about cognitions. Results suggest that certain sequences in social media content may predict cause of death and provide an estimate of when a social media user is likely to die by suicide.